Cell cycle regulators in Drosophila: downstream and part of developmental decisions. - Lehner, C.F.; Lane, M.E. (Journal of Cell Science, 1997)
The molecular identification of an evolutionarily conserved set of cell cycle regulators in yeast, Xenopus egg extracts, and vertebrate cell culture has opened up a new perspective for understanding the mechanisms that regulate cell proliferation during metazoan development. Now we can study how the crucial regulators of eukaryotic cell cycle progression, the various cyclin/cdk complexes (for a recent review see Nigg (1995) BioEssays 17, 471-480), are turned on or off during development. In Drosophila, this analysis is most advanced, in particular in the case of the rather rigidly programmed embryonic cell cycles that generate the cells of the larvae. In addition, this analysis has revealed how the mitotic cycle is transformed into an endocycle which allows the extensive growth of larvae and oocytes. In contrast, we know little about cyclin/cdk regulation during the imaginal proliferation that generates the cells of the adult. Nevertheless, we will also consider this second developmental phase with its conspicuous regulative character, because it will be of great interest for the analysis of the molecular mechanisms that integrate growth and proliferation during development.